Inhibin B levels in relation to obesity measures and lipids in males with different numbers of metabolic syndrome components (2016)
Introduction: Defective spermatogenesis and metabolic syndrome affect 2-4% and 12.4% of males respectively. Deficient testosterone levels due to increased conversion of testosterone to oestradiol have been demonstrated in males with the metabolic syndrome (MS) with limited pituitary and leptin contribution. Defective spermatogenesis is thus implicated in males with MS but is controversial. Inhibin B is a marker of spermatogenesis. This study aims at evaluating inhibin B levels and their relationship with obesity measures and lipids in males with different number of MS components. Materials and Methods: This is a preliminary prospective study in which a total of 106 apparently healthy males (30, 30, 30 and 16 males with 0, 1, 2 and ≥3 components of metabolic syndrome (NMSC) respectively) aged 19-64 years were purposely selected. Blood pressure (BP) and obesity measures (including visceral adiposity index (VAI) and body mass index (BMI)) were obtained by standard methods. Fasting plasma glucose (FPG), total cholesterol (TC), triglycerides and high density lipoprotein cholesterol (HDLC) were determined by enzymatic methods while low density lipoprotein cholesterol (LDLC) and the lipid ratios (TG/HDLC, TC/HDLC, LDLC/HDLC) were calculated. Inhibin B was analysed by enzyme linked immunosorbent assay (RayBiotech, Inc. USA). Data analysed using analysis of variance (ANOVA) and multiple regressions were significant at P <.05. Results: Inhibin B decreased significantly in males with 0 to 2 NMSC (P <.05). However, inhibin levels between males with 0 and ≥3 NMSC were similar. Age and inhibin B levels were also similar among the different classes of BMI (P>0.05). Inhibin B related positively with HDLC and TC but negatively with VAI, LDLC and TC/HDLC. Conclusion: Reproductive function appears protected in Nigerian males with MS. However, improvement in HDLC, LDLC, TC levels, VAI and TC/HDLC may enhance fertility potential especially in males with one or two MS components, probably through dietary modulation and physical activity.